Real-world evidence of the impact of obesity on residual teeth in the Japanese population: A cross-sectional study - Hayashi, Mayu; Morino, Katsutaro; Harada, Kayo; Miyazawa, Itsuko; Ishikawa, Miki; Yasuda, Takako; Iwakuma, Yoshie; Yamamoto, Kazushi; Matsumoto, Motonobu; Maegawa, Hiroshi; Ishikado, Atsushi (PLOS ONE, 2022)
Tooth loss is associated with nutritional status and significantly affects quality of life, particularly in older individuals. To date, several studies reveal that a high BMI is associated with tooth loss. However, there is a lack of large-scale studies that examined the impact of obesity on residual teeth with respect to age and tooth positions. We assessed the impact of obesity on the number and position of residual teeth by age groups using large scale of Japanese database. This was a cross-sectional study of 706150 subjects that were included in the database that combined the data from health insurance claims and health check-up, those lacking information about BMI, HbA1c level, smoking status, and the number of residual teeth were excluded. Thus, a total of 233517 aged 20-74 years were included. Subjects were classified into 4 categories based on BMI, and the number of teeth was compared between age-groups. The percentage of subjects with residual teeth in each position was compared between groups with obesity (BMI ≥25.0 kg/m2) and non-obesity. Logistic regression analysis was performed to clarify whether obesity predicts having <24 teeth. Higher BMI was associated with fewer teeth over 40s (P for trend <0.0001 when <70s). Obesity was associated with the reduction of residual teeth in the maxillary; specifically, the molars were affected over the age 30. Smoking status further affected tooth loss at positions that were not affected by obesity alone. After adjusting for age, sex, smoking status, and HbA1c ≥6.5%, obesity remained an independent predictive factor for having <24 teeth (ORs: 1.35, 95% CIs: 1.30-1.40). We found that an increase in BMI was associated with a decrease in the number of residual teeth from younger ages independently of smoking status and diabetes in the large scale of Japanese database.